The Effectiveness of Learning Media Exhibitions Through Project-Based Learning (PjBl) to Improve the Creativity Skills of Prospective Mathematics Teachers - Maharani, Rizqona; Lestari, Mulyaningrum; Abd Rauf, Rose Amnah; Hargrove, Benjamin Michael; Chong, Seng Tong; Listiani, Tanti; Exacta, Annisa Prima (Jurnal Pendidikan Matematika, 2023)
Prospective mathematics teachers in the IAIN Kudus mathematics education study program have not demonstrated maximum creative behaviour when developing learning media. Learning media exhibitions through project-based learning (PjBL) enable prospective teachers to interact directly (facilitate discussions)/be engaged authentically, explore critically, be innovative, elaborative, collaborative, and original, and gain challenging cognitive experiences so that their creativity increases. To determine the effectiveness of media exhibitions through PjBL on increasing the creativity of prospective mathematics teachers, a quasi-experimental approach was carried out on students (n=50) in the fifth semester of the 2022/2023 academic year of the IAIN Kudus mathematics education study program taken using cluster random sampling techniques. After applying this model and carrying out a paired t-test, there was a statistically significant difference between the mean of creativity of prospective mathematics teachers before and after implementing the PjBL model and exhibition activity. Meanwhile, the effectiveness of the improvement is 0.48 in the medium category. This means that the learning media exhibition through PjBL is effective in increasing the creativity of prospective teachers. Media exhibition activities through project-based learning can be a valuable and sustainable educational program to foster the creativity of prospective teachers majoring in mathematics education. Calon guru matematika pada program studi pendidikan matematika IAIN Kudus belum menunjukkan perilaku kreatif yang maksimal dalam mengembangkan media pembelajaran. Pameran media pembelajaran melalui pembelajaran berbasis proyek (PjBL) memungkinkan calon guru berinteraksi langsung (memfasilitasi diskusi)/terlibat secara autentik, bereksplorasi secara kritis, inovatif, elaboratif, kolaboratif dan orisinal, serta memperoleh pengalaman kognitif yang menantang sehingga kreativitasnya meningkat. Untuk mengetahui efektivitas pameran media melalui PjBL terhadap peningkatan kreativitas calon guru matematika, dilakukan pendekatan kuasi eksperimen pada siswa (n=50) semester V tahun pelajaran 2022/2023 pendidikan matematika IAIN Kudus program studi yang diambil dengan menggunakan teknik cluster random sampling. Setelah diterapkan model tersebut dan dilakukan uji t berpasangan, terdapat perbedaan yang signifikan secara statistik antara rata-rata kreativitas calon guru matematika sebelum dan sesudah penerapan model PjBL dan kegiatan pameran. Sedangkan efektivitas peningkatannya sebesar 0,48 dengan kategori sedang. Artinya pameran media pembelajaran melalui PjBL efektif meningkatkan kreativitas calon guru. Kegiatan pameran media melalui pembelajaran berbasis proyek dapat menjadi program pendidikan yang bernilai dan berkelanjutan untuk menumbuhkan kreativitas calon guru jurusan pendidikan matematika.